CORAL REEF MANAGEMENT IN TAKA BONERATE MARINE NATIONAL PARK, SOUTH SULAWESI (A CASE STUDY FOR THE ALTERNATIVE TO DESTRUCTIVE FISHING PRACTICES ON CORN REEFS) - S upriharyono (JOURNAL OF COASTAL DEVELOPMENT, 2001)
The coral reef is the most productive marine ecosystem in coastal waters. The primary productivity may reach up to more than 10 kg C/m2/year. This resulted in a high number of fisheries production, such as fishes, shrimps, lobster, mollusc (shellfish), turtle, and others. Unfortunately, this condition has already suffered from non-sustainable human use including destructive fishing practices (bombing and cyanide), coral mining, over fishing, settlement pollution and uncontrolled tourism development. These affected the production of those fisheries resources in coral reefs. In order to manage those resources, such alternative to destructive use need to be studied. This paper reports alternatives to destructive fishing practices on coral reefs. The study had been carried out at Taka Bonerate Marine National Park, the District of Selayar, South Sulawesi province, for about 3 weeks, 7-26 November 2000. Survey method was used during the study. The data were collected using Participatory Rapid Appraisal (PRA)’s method, with members of fisher group as the participants. Three kinds of reef fish groups are identified at the Taka Bonerate Islands waters, i.e. major group, target group, and indicator group. These include ornamental and consumption fishes. These were caught with several fishing gears, while some of them are identified as destructive fishing practices, e.g. bomb, cyanide fishing. However, some of them can be recommended as sustainable fishing technologies, i.e. (1) pancing cumi-cumi, (2) pancing tonda, and (3) samba/kulambi.